2010
DOI: 10.1080/07399331003599555
|View full text |Cite
|
Sign up to set email alerts
|

Do Women With Higher Autonomy Seek More Maternal Health Care? Evidence From Eritrea and Ethiopia

Abstract: Using data from the 2002 Eritrea and 2005 Ethiopia Demographic and Health Surveys (DHS), this study was carried out to investigate the link between women's autonomy and maternal health care utilization in relation to socioeconomic factors. Although some dimensions of women's autonomy are significantly linked to an increased likelihood of receiving health care, they do not emerge to be mediators of the link between socioeconomic factors and use of health services for antenatal care and delivery care. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 33 publications
1
82
0
Order By: Relevance
“…Mozambique was also unique in that 21% of women reported that "someframeworks [38,39] for statistically significant relationships to female healthcare autonomy. Education, age, and number of living children were all found to have significant associations (p < 0.05) and prior literature has also supported their relationship with women's empowerment [40][41][42]. These factors were thus included as adjustment variables in the multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Mozambique was also unique in that 21% of women reported that "someframeworks [38,39] for statistically significant relationships to female healthcare autonomy. Education, age, and number of living children were all found to have significant associations (p < 0.05) and prior literature has also supported their relationship with women's empowerment [40][41][42]. These factors were thus included as adjustment variables in the multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The common pattern was that women's empowerment increased the uptake of ANC and postnatal services. [6][7][8] However, the influence of women's empowerment on skilled delivery care was weak in Ethiopia/ Eriteria [9] and Nairobi, Kenya [10] but significant in Nigeria. [11,12] Aside from maternal healthcare utilisation, Adhikari et al, [13] and Desai and Johnson [14] reported that women's empowerment was also a significant independent predictor of child mortality.…”
mentioning
confidence: 99%
“…Woldemicael and Tenkorang (2010) analyzed the relationship between women's autonomy and health seeking behavior in Ethiopia and found that overall, more autonomous Ethiopian women were more likely to access health care compared to Ethiopian women with little household autonomy. Woldemicael (2010) further used Demographic and Health Survey data from Ethiopia and Eritrea to show that, net of socioeconomic-status, physical autonomy increased the use of antenatal care in both countries, though sole decision-making about household purchases increased antenatal care only in Eritrea. Singh et al (2012) also found that Nigerian women's decisionmaking abilities and negative attitudes towards wifebeating increased children's odds of being fully immunized, net of mother's education, work status, and household wealth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Greater women's autonomy has been linked to reductions in infant mortality (Castle 1995;Doan and Bisharat 1990), better child nutritional outcomes (Brunson, Shell-Duncan and Steele 2009;Dancer and Rammohan 2009), and increased use of health care services (Woldemicael 2010;Woldemicael and Tenkorang 2010) in both South Asia and SSA. However, little research has focused on the relationship between women's autonomy and children's immunization status (Singh, Haney and Olorunsaiye 2012), despite its recognized importance in improving children's health and odds of survival.…”
Section: Introductionmentioning
confidence: 99%